Does intraspecific competition cause oxidative stress? Influence of biotic and abiotic factors on antioxidant system of an invasive round goby - Dagmara Błońska; Ali Serhan Tarkan; Bartosz Janic; Mariusz Tszydel; Bożena Bukowska (Ecology and Evolution, 2023)
Abstract Changes in oxidative status represent organismal response to stressful external stimuli. While there is substantial knowledge on the influence of abiotic factors on the antioxidant system of different organisms, the impact of biotic factors remains largely unexplored. The aim of the present study was to evaluate the effect of acute competitive interactions on oxidative stress. Territory‐resident and intruder round goby Neogobius melanostomus individuals were experimentally subjected to competition for limited shelter resource in three treatments (lasting 1, 6 and 12 h), and oxidative stress parameters (total antioxidant capacity, catalase activity, reduced glutathione, lipid peroxidation), as well as behaviour (time spent in the shelter, guarding the shelter and aggression) were measured. All tested biochemical parameters reached higher values in the liver than in the muscle tissue. Fish behaviour and antioxidant defence did not show any potential relationships reflecting changes in antioxidant status and aggression. Particularly, there was no difference between resident and intruder fish in oxidative stress parameters. We compared our results to the outcome of our previous studies (similar experimental protocol and species) but with acute heat shock as a stressor instead of competition. The higher temperature was found to be a stronger stressor than the competition, most pronounced in total antioxidant capacity and oxidative damage.